Temporal and structural sensitivities of major biomarkers for detecting neuropathology after traumatic brain injury in the mouse - Xiong, Guoxiang; Jean, Ian; Farrugia, Anthony M.; Metheny, Hannah; Johnson, Brian N.; Cohen, Noam A.; Cohen, Akiva S. (Frontiers in Neuroscience, 2024)
Traumatic brain injury (TBI) is a leading cause of morbidity and mortality, especially in teenagers to young adults. In recent decades, different biomarkers and/or staining protocols have been employed to evaluate the post-injury development of pathological structures, but they have produced many contradictory findings. Since correctly identifying the underlying neuroanatomical changes is critical to advancing TBI research, we compared three commonly used markers for their ability to detect TBI pathological structures: Fluoro-Jade C, the rabbit monoclonal antibody Y188 against amyloid precursor protein and the NeuroSilver kit were used to stain adjacent slices from naïve or injured mouse brains harvested at different time points from 30 min to 3 months after lateral fluid percussion injury. Although not all pathological structures were stained by all markers at all time points, we found damaged neurons and deformed dendrites in gray matter, punctate and perivascular structures in white matter, and axonal blebs and Wallerian degeneration in both gray and white matter. The present study demonstrates the temporal and structural sensitivities of the three biomarkers: each marker is highly effective for a set of pathological structures, each of which in turn emerges at a particular time point. Furthermore, the different biomarkers showed different abilities at detecting identical types of pathological structures. In contrast to previous studies that have used a single biomarker at a single time range, the present report strongly recommends that a combination of different biomarkers should be adopted and different time points need to be checked when assessing neuropathology after TBI.